ANÁLISE DA CONTRIBUIÇÃO DO COACHING NA VIDA PROFISSIONAL DO INDIVÍDUO - GERMANO, MARIANA SIMÕES (2017)
This work approaches the contribution of the coaching to the individual professional development, concerning professional level outcomes and the conditions that may enhance or impair this process. Organizations are faced with an increasingly competitive environment; therefore, in order to stay ahead in their market, they need people with distinguished skills. The coaching emerged with the proposal to maximize the skills of the individuals and to contribute to the goals and results achievement. Thus, the major aim of this research is to verify if the coaching contributes with the individuals in order to reach their professional development aims. As specific objectives the research aims: to identify the reasons why people begin the coaching process; to analyze if the results, initially expected by the “coachee”, are reached after the coaching process; to analyze in which conditions the results are reached, especially regarding the coach and the “coachee” issues, their relationship and also the coaching process issues; to identify if, beyond the expected professional results, there is other benefits for the “coachee”. The research uses a qualitative approach with an exploratory character and the method used was the interview. Four groups participated of the research, each one was composed by one coach and one “coachee”, and they were questioned about their aims in searching for a coach, their reached results and also the general coaching process issues. From the interviews analysis, it was concluded that all “coaches” turned to the process by personal will and initiative. Three from the four respondents choose their coach through a friend indication. The reasons that motivated people to search for the coaching were the cost-benefit ratio, the pursuit of self-awareness and the professional and personal development. All the professional aims were reached, beyond these, other benefits emerged from the process were highlighted such as security, self-awareness, better time management, among others. Concerning the coaching process, it was possible to identify there is not a pattern of values charged by the coaches, neither time nor number of sessions applied. The interviewed pointed the issues of the “coaches” that contribute to the coaching process as being open to changes and wising to change, about the coaches issues, were identified the knowledge, love, impartiality, respect, among others.